Ответ:
1. 3x²-2(x+5)=2x²-10
3x²-2x-10=2x²-10
3x²-2x-10-2x²+10=0
x²-2x-0=0
D=2*2-4*0=4; √D=2
x1=2+2/2=2
x2=2-10/2=-2
Ответ:2
2.
![5 - {x}^{2} + (x - 3) \times (x + 3) \\ 5 - {x}^{2} + (x - 3) \times (x + 3) \\](https://tex.z-dn.net/?f=5%20-%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%28x%20-%203%29%20%5Ctimes%20%28x%20%2B%203%29%20%5C%5C%20)
![5 - {x}^{2} + {x}^{2} - {3}^{2} \\ 5 - {2.3}^{2} + {2.3}^{2} - {3}^{2} \\ 5 - 9 = - 4 5 - {x}^{2} + {x}^{2} - {3}^{2} \\ 5 - {2.3}^{2} + {2.3}^{2} - {3}^{2} \\ 5 - 9 = - 4](https://tex.z-dn.net/?f=5%20-%20%20%7Bx%7D%5E%7B2%7D%20%20%2B%20%20%20%7Bx%7D%5E%7B2%7D%20%20-%20%20%20%7B3%7D%5E%7B2%7D%20%20%5C%5C%205%20-%20%20%7B2.3%7D%5E%7B2%7D%20%20%2B%20%20%7B2.3%7D%5E%7B2%7D%20%20-%20%20%7B3%7D%5E%7B2%7D%20%5C%5C%205%20-%209%20%3D%20%20-%204%20)
Скобки сократили по формуле сокращённого умножения (а-б) *(а+б) =а*2-б*2
Потом получилось - 2.3*2+2.3*2 - сократили
И получилось 5-3*2
3*2=9
5-9=-4
Ответ:-4
3.2х+3х+4х=63
9х=63
Х=63:9
х=7
2*7=14
Ответ: 14 см.